Mutations in PCDH21 cause autosomal recessive cone-rod dystrophy - Ostergaard, Elsebet; Batbayli, Mustafa; Duno, Morten; Vilhelmsen, Kaj (Journal of Medical Genetics, 2010)
International audience Background: Cone-rod dystrophy is a retinal dystrophy with early loss of cone receptors and a parallel or subsequent loss of rod receptors. It may be syndromic, but most forms are non-syndromic and inherited in an autosomal dominant, autosomal recessive or X-linked recessive way. Methods and results: We identified a small consanguineous family with six patients with cone-rod dystrophy from the Faroe Islands. Homozygosity mapping revealed a single homozygous locus of 4.2 Mb on chromosome 10q23.1-q23.2, encompassing 11 genes. All patients were homozygous for a 1 bp duplication in PCDH21, c.524dupA, which results in a frameshift and a premature stop codon (p.Q175QfsX47). Conclusion: To our knowledge, this is the first report of mutations in PCDH21 as a cause of human disease. PCDH21 is highly expressed in the retinal photoreceptor cells. It encodes protocadherin 21, which belongs to the cadherin superfamily of large cell surface proteins characterised by a variable number of extracellular cadherin domains. A PCDH21 knockout mouse model has previously shown loss of photoreceptor cells and abnormal cone and rod function, similar to the findings in the patients.